2021
DOI: 10.33448/rsd-v10i7.16647
|View full text |Cite
|
Sign up to set email alerts
|

Intoxicação exógena em crianças devido ao uso de medicamentos no Brasil: Avaliação do perfil de notificações

Abstract: Introdução: A intoxicação exógena por medicamento acomete a população pediátrica através dos riscos de exposição e manuseio de fármacos nas residências, como: colocar medicamentos atrativos de fácil acesso às crianças e a superdosagem devido a má administração dos responsáveis. Objetivo: avaliar o perfil de notificações de intoxicação exógena em crianças envolvendo o uso de medicamentos no Brasil. Metodologia: Trata-se de estudo descritivo, exploratório e transversal utilizando dados do Sistema de Informação d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
1
2
0
3
Order By: Relevance
“…It is the fact that children move more easily at this age and are vulnerable to accidents, which may be a rationale for such a result. The surveyed age group corroborates the results obtained in another study carried out in the country, 18 with a gender-related difference, given that the study by Leite et al showed a higher occurrence of cases in boys.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…It is the fact that children move more easily at this age and are vulnerable to accidents, which may be a rationale for such a result. The surveyed age group corroborates the results obtained in another study carried out in the country, 18 with a gender-related difference, given that the study by Leite et al showed a higher occurrence of cases in boys.…”
Section: Discussionsupporting
confidence: 90%
“…Similarly to other studies, the home environment was the predominant site of exposure (95.76%), due to inadequate storage, the so-called home pharmacies, which facilitate access for children and adolescents. 18 , 19 A study conducted on children and adolescents found that education programs for parents and caregivers to prevent exposure to pharmacological drugs were not successful. Medicines continue to cause harm due to unsafe storage, which facilitates exposure and unintentional ingestion, in age groups under 5 years, and also the intentional ingestion of adolescents owing to misuse and abuse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Existem informações de que níveis baixos de atividade enzimática (CYP3A4) foram observados em crianças com apenas 3 meses de idade. Já para as enzimas da fase II, a ação da β-glucuronidase aumentará até os três anos (LEITE CEA, et al, 2021).…”
Section: Toxicocinética E Toxicodinâmica Em Criançasunclassified
“…A intoxicação exógena por erro de medicação tem ocasionado grande preocupação em dimensão mundial devido ao alto índice de ocorrência atrelado à grande incidência de danos que podem ser acarretados ao paciente durante os cuidados hospitalares. Nos Estados Unidos, estima-se que ocorre erro de medicação anestésica em uma proporção de um a cada 20 aplicações de medicação perioperatória, o que acarreta cerca de 2 milhões de erros anualmente 6 . As intoxicações medicamentosas possuem importância na saúde pública pela sua magnitude e pelo fato de ser um agravo que pode ser prevenido 2 .…”
Section: Introductionunclassified